Numerical modeling of delamination in composite panel under low-velocity contact with hail - V.T. Le; Т. V. Burnysheva (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
A technique is proposed to simulate multiple impacts of hailstones on composite panels based on a developed model and testing of low-velocity hailstone impacts. Using Instron 3369 and BiSS, compression tests were conducted on ice samples frozen at temperatures of –40°C, –30°C, and –20°C, respectively. Compressive strength and volumetric density were determined for each group. The elastic modulus ranged from 154 to 1214 MPa. Statistical data processing methods were applied to determine the variability intervals and average values of the elastic modulus for each interval at a freezing temperature of –20°C. Studies on hail impact on composite panels have highlighted delamination as a major failure mode. Based on experimental results, linear, quadratic, and cubic dependencies of damage (number of delaminated layers) on the composite plate when subjected to a 35mm diameter hailstone impact on the elastic modulus and velocity of the ice were computed. The maximum number of layers destructed is 16, which is 80% of the panel thickness at a velocity of 170m/s, with the ice's elastic modulus being 1250 MPa. Impact velocity significantly affects the composite panels damage susceptibility, with the material's elastic modulus having a weaker effect. Experimental findings show a significant correlation between impact speed and damage extent, with larger hailstones causing deeper delamination.